Second law analysis for optimal thermal design of radial fin geometry by convection - Taufiq, B.N.; Masjuki, Haji Hassan; Mahlia, T.M.I.; Saidur, Rahman; Faizul, M.S.; Niza Mohamad, E. (Applied Thermal Engineering, 2007)
This paper presents a second law analysis for the optimal geometry of fin array by forced convection. The analytical analysis involves the achievement of a balance between the entropy generation due to heat transfer and entropy generation due to fluid friction. In the design of a thermal system, it is important to minimize thermal irreversibilities because the optimal geometry will be found when the entropy generation rate is minimized. In this paper, the entropy generation rate is discussed and optimum thickness for fin array is determined on the basis of entropy generation minimization subjected to the global constraint. In addition, the influence of cost parameters on the optimum thickness of fin array is also considered and presented in graphical form. It has been found that the increase in cross flow fluid velocity will enhance the heat transfer rate that will reduce the heat transfer irreversibility.